Arquivos e sua importância para a preservação da memória: uma análise do Centro de Memória da Amazônia - SPANNER, Júlia Ramos (2021)
Archival study is increasingly expanding its scope, even if it is a relatively new área of research, much has been discussed about the basic principles of archival science, including the notion of archiving and its importance. In this regard, it raised the question about the importance of keeping memories, that is, the importance of the archive to society at large. Therefore, it was very important for this study to consider that the concepts of memory and archives are correlated, and because of this can not be dissociated. For this purpose, the Amazon Memory Center (CMA) and two projects developed in it (Immigration Project and Inquisition Project in the Amazon) were considered as a field of research, as well as a bibliographical research that took into consideration the memory-archive pair of which stand out monographic productions and national periodicals publications. With the theoretical information gathered, it was possible to understand the importance of memory in archives for the society of the State of Pará, since the inquisitorial processes and the immigration record stell a part of the Pará history and its formation. Without this information it would not be possible to specify the quantity or influences that the local culture suffered over time, nor to make known the descendants of these immigrants or the influences that the processes caused in the Pará society.